Immunity of tick-exposed seronegative and seropositive small stock challenged with two stocks of Cowdria ruminantium - Du Plessis, J L; Van Gas, L (Onderstepoort journal of veterinary research, 1989)
Nineteen per cent and 32% of serologically positive sheep and goats in heartwater endemic areas of the Republic of South Africa were susceptible to challenge with, respectively, the Ball 3 and Welgevonden stocks of Cowdria ruminantium. There was good correlation between the results of the indirect fluorescent antibody test and immunity, since without exception all the seronegative animals reacted when they were challenged. The fact that only 74% of the seropositive sheep and goats were immune to challenge can probably be ascribed to the poor cross-protection between stocks of C. ruminantium and not to false positive serological reactions.